Physiological and sanitary quality of seeds of Dimorphandra gardneriana Tul. treated with essential oils - Moura, Sueli da SIlva Santos de; Soares, Alinne Menezes; Ursulino, Marina Matias; Oliveira, Robério de; Nascimento, Luciana Cordeiro; Alves, Edna Ursulino (Comunicata Scientiae, 2018)
Dimorphandra gardneriana, popularly known as fava d’anta, is a medicinal species whose fruits and seeds are used in the manufacture of medicines. The objective of this study was to evaluate the efficiency of clove (Syzygium aromaticum (L.) Merr. & L.M. Perry) and copaíba (Copaifera sp.) essential oils in antifungal treatment of seeds of D. gardneriana and their influence on physiological quality of the seeds. Two experiments were carried out in a completely randomized design using seeds treated with different concentrations of copaiba and clove oils (0.5, 1.0, 1.5, and 2.0 mL) and two controls—seeds were treated with distilled water or fungicide. The variables analyzed were: incidence of fungi in seeds in the first experiment and seed germination and vigor (first germination, length and dry mass of root and shoot of the seedlings) in the second one. The incidence of fungi of the genera Aspergillus sp., Penicillium sp., and Rhizopus sp. in the seeds was elevated. The copaiba oil at the concentrations used did not satisfactorily reduce the incidence of fungi in the seeds of D. gardneriana, while the treatment of the seeds with clove oil at concentrations of 2.0 and 0.5 mL reduced the incidence of Penicillium sp. and Rhizopus sp., respectively. Seed germination and vigor increased at concentrations of 2 mL of clove oil and 1.25 mL of copaiba oil.